The Secessionist Movements in Southern Philippines Prospects and Challenges in Negotiating for the Mindanao Peace Process - D. HALILI JR., SERVANDO (ASIA PACIFIC JOURNAL OF SOCIAL INNOVATION, 2024)
This essay attempts to retrace the history of evangelical (aka protestant) Christian missionary work in Mindanao. Missionary work in the area started in Zamboanga by the Christian and Missionary Alliance, an organization originally based in Nyack, New York that has significantly shaped the cultural make up of Mindanao. Its history, however, has not been considered succinctly, especially during the formative years of missionary work. The paper narrated the difficulties and struggles faced by pioneer missionaries, especially those of the missionary couple David and Hulda Lund, and their eventual successes in converting Filipinos to evangelical Christianity, the establishment of evangelical churches and the foundation of a school that eventually evolved into the Ebenezer Bible College and Seminary, the first school of its kind in Mindanao.